Understanding and Promoting Effective Online Student Learning Styles: An Action Research Study - Patterson, James G. (My University, 2001)
Nine online students of a freshman-level computer survey course at a suburban Phoenix community college agreed to participate in a research project designed to increase the Independent learning style. Prior research has shown the Independent style is especially critical for online success. Early in the course, students filled out the general form of the Grasha- Riechmann Student Learning Styles Scales (GRSLSS) to provide a baseline measure of their learning styles. Following this, students were exposed to an online lecture on the importance and meaning of learning styles and received several online assignments designed to strengthen the Independent learning style. Then the same students were asked to fill out the specific form of the GRSLSS, used by past researchers to measure changes in learning styles. After a statistical "t" test was applied, the class showed a slight increase but no significant difference in the Independent learning style. However, two learning styles showed a significant drop: Collaborative and Competitive. Although this study did not show a significant difference in the Independent learning style, past research and experience shows that students with a higher Independent learning style have a greater chance at online learning success. Instructors should consider how they could help increase their students' Independent learning style through independent online activities.
Keywords: Independant Learning Styles; Online Learning Success